Public Cosmopolitanism vs State Nationalism: A Comparative Study of State and Public Responses to The Gaza Genocide Since 2023 - Masitoh, Dewi; Putri, Alfredha Shinta; Aswar, Hasbi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
The Israeli intervention that occurred in Gaza in 2023 caused a wave of reactions from countries and the global community, showing differences in orientation and approach. Since the war, the global public has shown a strong reaction to Israeli attacks on civilians and has demanded a ceasefire for humanitarian reasons. In contrast, states have been divided into those who joined to condemn Israel and others who supported Israel. This article comparatively analyses the response of the state and the international public to genocide in Gaza from the perspective of nationalism and cosmopolitanism. Nationalism focuses on prioritizing the state interest over others, whereas cosmopolitanism addresses individual rights as the most important thing in global politics. This study uses qualitative methods to interpret the varieties of the states and publics by collecting online documents from websites, journals, and media. This study found that countries tend to act based on national interests, geopolitical considerations, strategic alliances, and domestic stability. Even among Muslim countries and supporters of Palestine, the attitudes shown are often ineffective because they are shackled by domestic political and economic calculations. Instead, the global public displayed strong cosmopolitan solidarity through demonstrations, digital campaigns, and economic boycotts as a form of defence of human rights and universal justice. The tension between a nationalistic approach to the state and a cosmopolitan public response indicates a wide gap between the state and the public stance toward the Gaza genocide.